Brand Advocacy and Repurchase Intention of Malaysian Automotive Owners Using SEM Approach - Kwong, Simon C. M. (AeU, 2015)
The objective of this study was to relate the applicability of the TRA theory in the advocacy and repurchase intention of Malaysian automotive owners pertaining to their future purchases. Consequently, it was found that perceived brand perception of equity, value, affective and continuance commitment had significant influence in the advocacy and repurchase intentions of auto owners in their future auto purchases. These findings were similar with many past findings (Tolba, 2006; Aaker, 2004; Johnson et al, 2006; Keller, 2003; Fornell et al, 1996; Parasuraman et al, 1996). The findings also highlighted that there were no significant influence for value on satisfaction and satisfaction on affective & continuance commitment of the advocacy and repurchase intention of the auto owners. The findings also found that Malaysian brand automotive owners were quite loyal to the local brand because the “switching cost” is a huge barrier. Due to such an advantage the Malaysian automotive industry should capitalize on this nationalistic sentiment among the existing customers though the product quality was left much to be desired. The Malaysian Automotive Industry should ensure that product attributes must meet basic quality standards in order to retain existing customers as well as attract new purchasers.